The Effect of Interdialytic Combined Resistance and Aerobic Exercise Training on Health Related Outcomes in Chronic Hemodialysis Patients: The Tunisian Randomized Controlled Study - Frih, Bechir; Jaafar, Hamdi; Mkacher, Wajdi; Ben Salah, Zohra; Hammami, Mohamed; Frih, Ameur (Frontiers in Physiology, 2017)
Background: Tunisia has the highest prevalence of hemodialysis patients compared to the other countries in North Africa. Dialysis centers rarely offer an exercise program to prevent physiological and psychological dialysis therapy–related alterations in chronic hemodialysis patients. Aim: To examine the impact of combined endurance–resistance training program on physiological and psychological outcomes in patients undergoing hemodialysis. Methods: We designed a single blinded, randomized, controlled study for a period of 4 months. Patients were randomized to intervention group or control group. Intervention group’ patients received four training sessions per week, held on non–hemodialysis days for a period of 4 months, whereas control group’ patients continued their regular lifestyle practice without direct intervention from the personnel of this investigation. Patients were evaluated at baseline (initial assessment) and after the 4–month study period (final assessment) by the same investigator blinded to the treatment group assignment using a physical testing battery, physiological, and psychological assessments. Results: Compared with control group, intervention group showed significant improvement in physical performance during the sit–to–stand–to–sit tests (STS–10: -16.2%, ES = -1.65, STS–60: +23.43%, ES = 1.18), handgrip force task (+23.54%, ES = 1.16), timed up and go test (-13.86%, ES = -1.13) and six–minute walk test (+15.94%, ES = 2.09). Likewise, mini nutritional assessment long form scores after intervention period were significantly higher in the intervention group compared to the control group (ES = 1.43). Physical and mental component scores of SF–36 questionnaire increased significantly in the intervention group (ES = 1.10, and ES = 2.06, respectively), whereas hospital anxiety and depression scale scores decreased significantly (ES = -1.65, and ES = -2.72, respectively). Regarding biological parameters, intervention group displayed improvement in systolic and diastolic blood pressures (ES = -2.77, and ES = -0.87, respectively), HDL–cholesterol, LDL–cholesterol and triglycerides systematic levels (ES = 1.15, ES = -0.98, and ES = -1.01, respectively); however no significant effect of intervention period was observed on C–reactive protein, hemoglobin, albumin and total cholesterol levels (P > 0.05). Conclusion: The current study showed that combined endurance–resistance training program had a beneficial impact on physical capacity and quality of life in chronic hemodialysis patients.